Dynamical characterization of rainfall structure and induced-attenuation over coastal regions of south Africa for earth-space links applications - Olurotimi, Elijah Olusayo; Ogudo, Kingsley; Alonge, Akintunde (Edelweiss Applied Science and Technology, 2025)
Rainfall structure characterization and the corresponding induced attenuation are crucial for accurately predicting signal outages in Earth-space propagation links, hydrology, and meteorology. This paper analyzes five years of data on 60-minute integrated rainfall collected from the South African Weather Service across three coastal locations in the Republic of South Africa, with applications in radio wave communication. The study employs recommendations from the International Telecommunication Union Radiocommunication Sector to convert higher 60-minute integration data to 1-minute intervals and to determine the rain height necessary for predicting rain-induced attenuation in Earth-space links. The results confirm that oceanic currents influence rainfall structure at these locations. The derived 1-minute rainfall rates correspond to different percentages of time, including the lower percentage of 0.01% for internet access and the even lower percentage of 0.001% required for multimedia applications. The 0.01% time percentage was used to verify rain-induced attenuation at higher frequency bands, emphasizing the importance of precise rainfall characterization for reliable communication system design and meteorological analysis.